MATERIALS USED IN PROSTHETIC (ORTHOPEDIC) DENTISTRY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background. Prosthetic dentistry relies on a wide range of materials designed to restore function, aesthetics, and structural integrity of the dentition. The selection of appropriate materials is a critical factor determining the success and longevity of prosthetic restorations.Objective. To review the principal materials used in prosthetic dentistry and evaluate their clinical significance, physical properties, and practical applications. Materials and Methods. A literature-based analytical review was conducted, focusing on contemporary dental materials utilized in prosthetic dentistry. Results. Modern prosthetic dentistry utilizes diverse material groups, including metals and alloys, ceramics, polymers, composites, impression materials, and luting agents.Conclusion. The continuous development of dental materials has significantly improved prosthetic treatment outcomes.
Keywords: Prosthetic dentistry, dental materials, ceramics, alloys, polymers, composites.